Usability of Procedure Text Material Teaching Modules Based on The PBL Model in Elementary Schools - Riyadi Rafiki; Tatang Muhtar; Tita Mulyati; Iim Siti Karimah; Yoga Prima Putra; Farida Amalia (CV. Ksatria Siliwangi, 2024)
Learning in elementary schools has an important role in forming the foundation of students' critical, creative and collaborative thinking abilities. One of the materials in learning Indonesian that is relevant for practicing these skills is procedural texts. The problem-based learning (PBL) model has been proven to be an effective approach in increasing student engagement. This research aims to analyze the usability of PBL-based teaching modules on procedural text material in elementary schools. The results of this research are the highest Feedback (UB) value, with a value of around 0.646%. This indicates that the Feedback variable (UB) is able to explain around 64% of the variables of the indicators. In contrast to the other side, the lowest value of the User Self Control (KDP) variable is seen in the variable which is only around 0.114. This shows that the motivation variable can only explain almost 11% of the variance of the indicators. Overall, this diagram provides an overview of how well each variable or construct is able to explain the variables of its indicators.